A rare foreign body in the stomach: A case report - Gültürk, Barış; Bozdağ, Ahmet; Kanat, Burhan Hakan; Girgin, Mustafa; Gülaçti, Umut (Logos Medical Publishing, 2013)
In many anxious adult patients admitted to the emergency centers because of intake of foreign bodies, small items, such as a needle is known to be ingested. In patients who swallowed foreign bodies, which are not penetrated outside of the gastrointestinal tract, and thus not accompanied by peritonitis, generally accepted approach is non-surgical approach and follow-up of the patient. We tried to analyze gastric foreign bodies in consideration of the patient who was not aware of a swallowed foreign body which could not possibly pass out of the gastrointestinal tract spontaneously. © 2013, Logos Medical Publishing. All Rights Reserved.
Midede ender bir yabancı cisim: Olgu sunumu
Keywords: Foreing body; Stomach